Performance Analysis of EPC Material as a Kidney Organ Phantom with Exposure Voltage Variations and PA-GF-Based Kidney Stone Size - Cari Cari; Mohtar Yunianto; Fuad Anwar; Hardo Ardiansyah Gilang Permadi (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Research in the field of radiodiagnostics has been extensively developed, creating the need for substitute objects to represent human organs—namely, radiological phantoms. A phantom is a simulated model of an organ fabricated using 3D printing technology. This study aims to evaluate the suitability of Expanded Polyamide – Glass Fiber (EPA-GF) as a kidney stone phantom material embedded within a kidney phantom, based on parameters such as material density, CT number, electron density, and radiation dose across various CT scan exposure voltages. The phantom samples were printed using a dual-extruder 3D printer, with Expanded Polycarbonate (EPC) used as the kidney phantom material. CT scan exposure voltages were set to 80 kV, 100 kV, and 120 kV. Kidney stone sizes used in this study ranged from 1 mm to 8 mm (1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, and 8 mm). The measured density of EPA-GF was 1.51 ± 0.06 g/cm³. The CT numbers obtained at each voltage were 373.30 HU, 329.05 HU, and 299.46 HU, respectively. The corresponding electron density values were 1.231, 1.210, and 1.196, respectively. The effective doses measured at each voltage were 0.0240 mSv, 0.0448 mSv, and 0.0798 mSv. All parameter values were found to be closely aligned with literature references. The smallest visible kidney stone size detected was 2 mm.